Adoption of IPM Practices in Grape, Tree Fruit, and Nut Production in the Western United States. (29th April 2016) - Farrar, J. J.; Baur, M. E.; Elliott, S. F.
Abstract: To determine the prevalence of IPM adoption in perennial crop production in the Western United States, this review examined peer-reviewed scientific literature, extension reports, and studies conducted by or on behalf of commodity groups or other agriculture interests that were published since the year 2000. Based on 32 sources of data, IPM adoption is widespread in production of tree fruits, nuts, and vines, with a large percentage of growers using many prevention, avoidance, monitoring, and selective-suppression practices – known as the PAMS approach. In the wine grape industry in California, quarantine, certified disease-free planting material, and leaf pulling are practiced broadly to prevent or avoid disease. Wine grape growers in California monitor frequently to track insect vectors of disease and employ area-wide management practices. Seventy to ninety percent of California pear growers and >90% of Oregon and Washington pear producers monitor for insect pests. Hazelnut, walnut, and almond production in Oregon and California rely heavily on pest-control professionals to monitor pest activity. Across a wide range of crops, infrastructure to model pest population development based on weather data are well established and depended upon by producers. Suppression using pesticides has declined drastically (from 40–90%) in Oregon hazelnut production, California almond and fresh-market grape production, and California, Oregon, and Washington pear production. Sixty to seventy percent of walnut and pear producers in California, Oregon, and Washington are considering the impacts to human health and environment when making suppression and management decisions. Western perennial crops and practices are unique, and the findings documented in this review may not be applicable nationally.